Stigma Music of Human Life in Indonesia Orchestral Music - Simanullang, Pernandus (PROMUSIKA, 2021)
Music continues to surround human life from time to time; music is inextricably linked to human life from the moment man is born. Music also plays a role in bringing changes to human life in a better direction and maybe vice versa. In our daily lives, we cannot avoid the sounds or vibrations that come to our ears through the strains of music. Our lives are approached by music wherever we are. Music is a part of our lives. The researcher here wants to find out more about how the music process develops over time and its stigma to the operation of social change in society with the concept of musicology with qualitative methods, where the stigma of music tends to go, how researcher wants to better understand music by using methods of theoretical anthropological studies from time to time until the birth of music, on the other hand, what changes happen after the music is born. Stigma against music has certainly affected social life in society. Stigma towards more popular music such as orchestral music is one of the music whose bearer style is more likely to be passionate in the listener. Here the author wants to invite the music listener community to hear and explore the meaning of music and bring an appreciation stigma to his life. In addition, the author seeks to confirm that the music listener community can listen and explore the meaning of music and bring a positive stigma to his life. In addition, the author also would like the songwriters to explore more songs that stigmatize music by continuing to support people's appetite for a better humanity.